Meningkatkan Kemampuan Berhitung Permulaan Anak Usia Dini melalui Media Abakus Kelompok B TK PGRI 2 Mataram - Suarni, Ni Luh (Lembaga Yasin AlSys, 2022)
The goal to be achieved in this study is to improve early childhood numeracy skills through Media Abakus Group B TK PGRI 2 Mataram in the 2021/2022 school year. The subjects of this study were 19 students of group B TK PGRI 2 Mataram, consisting of 8 female students and 11 male students. This research uses action research in two cycles consisting of four stages, namely: design, activity and observation, reflection. From all the action research activities of group B TK PGRI 2 Mataram students, namely being able to understand the ability to count addition and subtraction carried out in three cycles, it can be concluded that the learning outcomes of students in the BTK PGRI 2 Mataram group in the 2021/2022 school year, using the Abakus media can improved by the final result of the study is the average value of the class before the action is 63.79 or classical completeness 52.63%, becoming 69.16 or classical completeness 68.42% in the first cycle, increasing to an average of 72.00 or 78, 95% in the second cycle and increased to a test average of 82.53 or 100% in the third cycle.